2022
DOI: 10.1016/j.medj.2021.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential immunogenicity of homologous versus heterologous boost in Ad26.COV2.S vaccine recipients

Abstract: Background Protection offered by coronavirus disease 2019 (COVID-19) vaccines wanes over time, requiring an evaluation of different boosting strategies to revert such a trend and enhance the quantity and quality of Spike-specific humoral and cellular immune responses. These immunological parameters in homologous or heterologous vaccination boosts have thus far been studied for mRNA and ChAdOx1 nCoV-19 vaccines, but knowledge on individuals who received a single dose of Ad26.COV2.S is lacking. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 58 publications
(68 reference statements)
10
32
0
Order By: Relevance
“…The robust vaccine-induced T cell response was exclusively mediated in inactivated vaccine recipients by CD4 T cells. In contrast, individuals vaccinated with mRNA and non-replicating adenoviral vectored Spike vaccines are capable of inducing both CD4 and CD8 T cell responses as shown previously 10,[49][50][51] , and by our own data. Our results are in contrast with previous observations by other groups that showed the ability of inactivated vaccines to induce both CD4 and CD8 T cell response but are however in line with other data of T cell response observed in other inactivated viral vaccines 52,53 .…”
Section: The Importance Of Eliciting a Multi-antigenic T Cell Respons...supporting
confidence: 85%
“…The robust vaccine-induced T cell response was exclusively mediated in inactivated vaccine recipients by CD4 T cells. In contrast, individuals vaccinated with mRNA and non-replicating adenoviral vectored Spike vaccines are capable of inducing both CD4 and CD8 T cell responses as shown previously 10,[49][50][51] , and by our own data. Our results are in contrast with previous observations by other groups that showed the ability of inactivated vaccines to induce both CD4 and CD8 T cell response but are however in line with other data of T cell response observed in other inactivated viral vaccines 52,53 .…”
Section: The Importance Of Eliciting a Multi-antigenic T Cell Respons...supporting
confidence: 85%
“…The hierarchy of the magnitude of the memory CD4 + T cells was mRNA-1273>BNT162b2~NVX-CoV2373>Ad26.COV2.S. These overall findings are consistent with previous reports on COVID-19 vaccine T cell responses (Barouch et al ., 2021; Goel et al ., 2021; Guerrera et al, 2021; Khoo et al, 2022; Liu et al, 2022; Mateus et al ., 2021; Rodda et al, 2022; Tarke et al, 2022), but the analysis reported herein extensively expand these observations, including four different vaccines representing three different vaccine platforms, and with longitudinal data and single-cell cytokine expression resolution providing insights regarding CD4 + T cell subpopulations between the vaccines. Interestingly, multifunctional CD4 + T cells were observed most frequently after mRNA-1273 immunization, and CD4-CTLs represented a substantial fraction of the memory CD4 + T cells after mRNA-1273, BNT162b2, or NVX-CoV2373 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…We and others had previously reported enhanced neutralization capacity early after heterologous ChAd-BNT vaccination compared to homologous BNT-BNT-vaccination, both of which in turn induced clearly higher neutralizing antibody titers than a homologous ChAd vaccination regimen [3][4][5][6][7][8][9][10][11][12] . Apart from significant waning of neutralization capacity towards WT virus at late time points for all regimens, we here observed that differences in humoral immunity towards WT virus between ChAd-BNT and BNT-BNT vaccination vanished, while homologous ChAd-ChAd still showed reduced neutralization titers compared to the other two vaccination schemes.…”
Section: Discussionmentioning
confidence: 70%
“…We and others have previously shown that the heterologous combination of ChAd and mRNA vaccination results in a non-inferior or even superior humoral and cellular immune response compared to homologous mRNA or ChAd vaccination regimens [3][4][5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 97%